Capacidade biossortiva de leveduras saccharomyces cerevisiae em contato com corante violeta cristal e viabilidade de uso na indústria têxtil - Melo, Ludmilla Fernanda Arantes (2021)
Since the Industrial Revolution, textile manufacturing has gained more agility due to investments in technology and improvement of machinery, becoming a faster, mechanized production and with the final volume obtained on a large scale. Due to the increase in industrial activities, there are consequences to the environment, which are often cumulative and worrying. Natural resources are limited, and the elease of waste into the tributaries is mostly toxic with irreversible damage and affects biodiversity, triggering ecological imbalances. Products remaining from the production of textile industries are constantly inserted into effluents, thus, there are several studies aimed at reducing the amount of dyes present in aqueous bodies, since these substances are extensively used.Violet a Cristal dye presents various applications and purposes that it has in the textile industry. Therefore, the work tested the biosorption capacity of Saccharomyces cerevisiae yeasts in contact with violet crystal dye. Yeast was selected because it has low biological risk to humans, low cost of obtaining, it is easy to handle and culture. The parameters optimized to obtain greater absorption were: pH of the medium, yeast concentration, contact time and agitation. It was further tested whether partial yeast additions would be more effective than a single addition. To monitor the biosorption of the dye by yeast, spectrophotometric readings were performed at the maximum absorbance wavelength (585 nm) of violet crystal dye. Among the pH tested, 2.5; 4,5; 6.5 and 8.5, pH 2.5 was the most harmful in yeast action and the most effective for reducing absorbance was 4.5. In the addition of yeast, in a unique way, the best result for absorbance reduction was with a concentration of 0.75% m/v. The studied times were 30, 60, 90 and 120 minutes. The time of greatest absorbance reduction was 60 minutes. The long hems caused yeast damage. Removal percentages ranged from 71 to 96% with an average of 83.5%. In another yeast concentration study, adding it in sequential percentages of 0.25% m/v every 60 minutes to a total of 1.0% m/v, with agitation only in the last 60 minutes, 3% more dye reduction was obtained compared to the concentration of 0.75% (optimized value), applied at once. Finally, the work is a collaboration for a better understanding of the biosorctive action of saccharomyces cerevisiae yeast against violet crystal dye.